2017
DOI: 10.1371/journal.pone.0177531
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative family risks across income levels predict deterioration of children’s general health during childhood and adolescence

Abstract: Family is considered an important agent in the health development of children. This process is significant but quite complex because the prevalence of potential risk factors in the family can hinder children’s health. This study examined if multiple family risks might have cumulative effect on children and youth’s health across various levels of household income. The data in this study were drawn from the 2011–2012 U.S. National Survey of Children’s Health (N = 79,601). A cumulative family risk (CFR) index was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 74 publications
(82 reference statements)
0
15
0
Order By: Relevance
“…Previous research has recognised the empirical challenges of trying to comprehensively assess the ways in which risk factors co-occur. One approach is the use of cumulative risk indices, which quantifies the number of risks present in a child’s life and establishing associations to a range of outcomes, such as educational attainment, health and wellbeing [35]. This approach is based on the assumption that it is the accumulation rather than the content of the risk factor that matters most in shaping children’s development.…”
Section: Constellations Of Family Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has recognised the empirical challenges of trying to comprehensively assess the ways in which risk factors co-occur. One approach is the use of cumulative risk indices, which quantifies the number of risks present in a child’s life and establishing associations to a range of outcomes, such as educational attainment, health and wellbeing [35]. This approach is based on the assumption that it is the accumulation rather than the content of the risk factor that matters most in shaping children’s development.…”
Section: Constellations Of Family Riskmentioning
confidence: 99%
“…Cumulative risk indices involve identifying a set of risk factors (e.g. low maternal education, parental worklessness, teen parenthood, maternal depression), dichotomizing them (as extant or not) and adding them to derive a risk score for each individual in a given sample, combining multiple risks into a single index [3, 5]. Using a cumulative risk index does however not consider how different risk factors combine in individual lives and how they work together in shaping developmental outcomes.…”
Section: Constellations Of Family Riskmentioning
confidence: 99%
“…Previous research has explored the relationship between family factors (e.g., family cohesion, parent distress) and symptom burden as well as health-related quality of life, and found that family and parent factors are related to health outcomes [39]. The relationship between family risk and child health has been well-established in the general population [40,41]. Results of this work have called for a need to identify interventions focused on family function and parent distress as potential moderators of child health, although interventions focused on parent or family functioning within pediatric oncology are relatively rare [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the existing literature used cross-sectional designs that demonstrated the association of CHLPF with health outcomes at a specific point in time. 16 Thus, a longitudinal follow-up study that would investigate the associations between major variables 6 is warranted to examine the long-term implications of these practices.…”
Section: Introductionmentioning
confidence: 99%
“…For children, the family is a major socialiser that forms an important proximal environment for developing routines, capacity, knowledge and norms for healthy living. 6–8 If begun in early childhood, these familial factors can, in response to risks and adversities, promote positive health outcomes and reduce negative outcomes for children. 9 Because family is involved in daily health promotion for children, 10 the family context and its embedded routines are essential for shaping children’s health, health behaviour and lifestyles during growth.…”
Section: Introductionmentioning
confidence: 99%